Pendampingan Pemenuhan Kewajiban Pajak Orang Pribadi dan Badan di Kota Batam - Lanniari HS, Rizki; Kurniawan, Dedi; Arniati, Arniati; Anjelina, Anjelina; Hasanah, Afriyanti; Parinduri, Annisya Fitri Khairina (Politeknik Negeri Batam, 2023)
All individuals, organizations and business entities have tax obligations, but not all of them have knowledge and understanding of taxation. Fulfilling tax obligations is often an obstacle for individual and corporate taxpayers because it requires special knowledge related to tax administration. This is where the role of universities is needed in providing socialization and assistance regarding tax obligations. In 2022, Polibatam has developed an educational version of the tax e-filing application which is now ready to be used in outreach activities and assistance in fulfilling tax obligations for individual and corporate taxpayers in Batam City. It is hoped that this service activity can help resolve problems in the community, especially regarding fulfilling the tax obligations of OP taxpayers and corporate taxpayers in Batam City as well as increasing tax compliance by implementing Polibatam's educational version of the tax e-form application. It can be concluded that the response of the taxpayers who were accompanied was very positive towards the service activities carried out. In the satisfaction questionnaire filled out by taxpayers, 100% of taxpayers answered that they were willing to return to participate in other service activities that would be held by Polibatam in the future.